A proszociális viselkedés fejlődése és fejlesztése kisgyermekkorban - Hegedűs, Szilvia (Magyar Pedagógia, 2016)
Social and emotional competence in early childhood is an essential basis for children’s later school success. Accordingly, acquisition of prosocial behaviours (helping, sharing, cooperating, supporting, protecting, worrying, calming, compensation, compliance, compassion, etc.) is also an important task in social development. The components of prosocial, altruistic behaviour have been explored internationally in recent years. Unlike earlier research, these studies (Vaish, Carpenter,& Tomasello, 2009; Brownell, 2013; Thompson & Newton, 2013; Henderson, Wang, Matz,&Woodward, 2013) are increasingly focusing on early childhood and provide new findings that disprove certain cognitive psychological theses. The first part of the study presents the main approaches of prosocial behaviour, which mostly come from various psychological fields. Behavioural responses to another person’s needs play a significant role in the development of prosocial behaviour. Thus, we need to pay attention to the development of early characteristics of empathy and sympathy. Recent research has shown that within social and emotional skills we need to focus on the development of prosocial behaviour. In Hungary, the majority of the interventions for social skills focus on children of school age, but there are several international programmes (e.g. Second Step) which serve children as early as preschool in developing the social and affective fields. These programmes are already in place and show the importance of and need for more research to recognize opportunities to develop prosociality which can help us to devise Hungarian intervention programmes.